Position on The Arrangement of Administrative Sanctions By The KPPU Institution In State Science - Alsyam (Ekasakti Journal of Law and Justice, 2024)
The position of the Business Competition Supervision Commission as a business competition court in imposing administrative sanctions (administration Punisment) to the guilty perpetrator. Looking at the constitutional system in a state institution in Indonesia, it has its own proportional functions in law enforcement. According to Article 36 letter i of Law Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Business Competition that "Imposing sanctions in the form of administrative action on business actors who violate the provisions of this Law”. However, according to the provisions of this rule in Article 44 paragraph (2) that "Business actors can submit objections to the District Court no later than 14 (fourteen) days after receiving notification of the decision”. Types of research in legal writing will be carried out using normative legal methods (doctrinal research) or called Studi dogmatic. The research approach uses the Law approach (statue approach), case approach (cases approach), and analytical approaches (analitycal approach).  The research results explain that First, Constitutionally, the KPPU institution, given the task of adjudicating a report, assists the role of the judiciary in enforcing unfair business competition law. This is of course that in state administration there are still different roles in each institutional structure in Indonesia. Second, basically the role of the KPPU institution where the imposition of sanctions is administrative in the sense of carrying out supervision of the Antimonopoly Law based on the specific duties of the Law. Third, The KPPU's position as an independent institution in enforcing business competition law is Punitive  which is given to business actors based on the results of the inspection. The KPPU provides administrative sanctions as a preventive measure against the reported parties who engage in unfair business competition.